Investigation of the effects of energy density in Laser Sintering of polypropylene on morphological and dielectric properties for high-frequency antennas - Romeis, Manuel; Ehrngruber, Michael; Drummer, Dietmar (Procedia CIRP, 2024)
Advancements in the Internet of Things demand more capable antenna systems, which benefit from the complex geometries enabled by additive manufacturing. Novel approaches, such as external metallization of polymers, enable the design of these geometries but require the processing of low dielectric-loss polymers in additive manufacturing. Arising from prevailing limitations on additively manufactured low-loss components, this study investigates the effect of energy density on polypropylene's dielectric properties in powder bed fusion processes. Variations in laser power significantly influenced material density and mechanical characteristics. Both insufficient and excessive energy densities resulted in lower quality parts due to issues like fused particles or inadequate melting. Optimal dimensional accuracy and surface quality were achieved with energy levels slightly below those for peak density. While dielectric loss remained mostly stable, relative permittivity decreased at very low densities, where partial melting occurred. Relying on derived optimized parameters, the functionality of passive high-frequency components was demonstrated.
CRIS-Team Scopus Importer:2024-09-27
Keywords: high-frequency antenna; Laser Sintering (SLS); polypropylene